Penerapan Mobilisasi dalam Pencegahan Dekubitus dengan Jam Mobilisasi pada Lansia Stroke di RSUD Kabupaten Sragen - Melyana Okta Apriani; Erika Dewi Noorratri; Waluyo Waluyo (Pusat Riset dan Inovasi Nasional, 2023)
Background: The majority of stroke patients are in the age range of 55 years old and above. Someone who suffers from a stroke and does not immediately get assessed may experience changes in mental status, impaired speech due to facial paralysis, visual perceptual disturbances, and body paralysis, which can lead to the development of decubitus ulcers. Decubitus ulcers occur resulting from the prolonged pressures on the soft tissues that happen on bony areas against solid surfaces. The prevention of decubitus ulcers involves repositioning and mobilization. Repositioning or mobilization can also improve muscle strength and promote independence. Objective: The aim of this study is to describe the comparative final outcomes between two respondents in terms of the scale of decubitus risk before and after the implementation of mobilization. Method: A descriptive research design with a case study approach, conducted on two respondents. Results: Before the implementation of mobilization, both respondents were at moderate risk of developing decubitus ulcers. After repositioning every two hours for six days, both respondents had a low scale risk of developing decubitus ulcers and decubitus ulcers can be prevented. Conclusion: Mobilization has an influence on the degree of decubitus ulcers development in elderly stroke patients.